The fibrin technologies in acceleration of damaged bone regeneration in experiment - I. V. Maiborodin; B. V. Sheplev; M. N. Drovosekov; I. S. Kolesnikov; M. S. Toder; А. A. Shevela (Бюллетень сибирской медицины, 2012)
The processes of regeneration of the damaged rat bottom jaw bone after application of enriched platelets a fibrin clot were studied by morphological and radiovisiographic methods. After operation with use of fibrin technologies already after 1 week the bone tissue defect is filled by the merged islets of again generated bone. By second week after fibrin use the further formation of bone tissue in defect and formation of a bone callosity is noted.